Impact Of Services, Marketing And Halal Tourism On Tourism Recovery Strategies During The Covid-19 Pandemic - slamet heri winarno (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
The arrival of the covid-19 pandemic has made many places affected, one of which is the tourism industry. Ministry of tourism and creative economy is planning that halal tourism can help tourism become better, because halal tourism is currently in demand by many people because it is prospective and very potential also supported by many residents who are majority Muslim. To encourage this, the need for a maximum strategy in restoring tourism that has been declining from various aspects such as visits that affect income, and one of these efforts is service. Service is very important to be optimized, because the quality of excellent service will make guests more comfortable in visiting tourist attractions. If connected with halal tourism that the concept looks to be able to apply a very friendly service with the aim of being able to provide their needs and desires when traveling supported by amenity development strategies, attraction development, accessibility development, HR development, and friendly tourism that applies sharia principles. The method used is quantitative data in the form of primary data resulting from the dissemination of questionnaires directly to tourists who visit.